Ulcerative Colitis-associated E. coli pathobionts potentiate colitis in susceptible hosts. Issue 1 (9th November 2020) - Yang, Hyungjun; Mirsepasi-Lauridsen, Hengameh Chloé; Struve, Carsten; Allaire, Joannie M.; Sivignon, Adeline; Vogl, Wayne; Bosman, Else S.; Ma, Caixia; Fotovati, Abbas; Reid, Gregor S.; Li, Xiaoxia; Petersen, Andreas Munk; et al.
ABSTRACT: Ulcerative colitis (UC) is a chronic inflammatory condition linked to intestinal microbial dysbiosis, including the expansion of E. coli strains related to extra-intestinal pathogenic E. coli . These "pathobionts" exhibit pathogenic properties, but their potential to promote UC is unclear due to the lack of relevant animal models. Here, we established a mouse model using a representative UC pathobiont strain (p19A), and mice lacking single immunoglobulin and toll-interleukin 1 receptor domain (SIGIRR), a deficiency increasing susceptibility to gut infections. Strain p19A was found to adhere to the cecal mucosa of Sigirr -/- mice, causing modest inflammation. Moreover, it dramatically worsened dextran sodium sulfate-induced colitis. This potentiation was attenuated using a p19A strain lacking α-hemolysin genes, or when we targeted pathobiont adherence using a p19A strain lacking the adhesin FimH, or following treatment with FimH antagonists. Thus, UC pathobionts adhere to the intestinal mucosa, and worsen the course of colitis in susceptible hosts.